1994
DOI: 10.1002/ppul.1950170109
|View full text |Cite
|
Sign up to set email alerts
|

Role of adenosine in the hypoxic ventilatory response of the newborn piglet

Abstract: The role of intracerebral adenosine levels in the control of ventilatory response to hypoxia was explored in 15 spontaneously breathing intubated piglets, 1-5 days old, sedated with chloral hydrate. Respiration was recorded via by a pneumotachograph. In all animals exposed to hypoxia (12% O2) for 10 minutes. There was an initial increase in ventilation followed by a late decrease (the biphasic ventilatory response). Both intravenous caffeine citrate (20 mg/kg) and an FiCO2 of 0.05 separately abolished or atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In respiratory networks, adenosine is clinically significant because it depresses ventilation (Herlenius et al, 1997;Herlenius and Lagercrantz, 1999;Mironov et al, 1999), and is implicated in the hypoxia-induced depression of ventilation (Yan et al, 1995) and apnea in newborns (Runold et al, 1989;Lopes et al, 1994). Our observation that the post-ATP decrease in frequency depends on ATP breakdown suggests that effects of ATP on rhythm will be determined by an interaction between P2 and P1 receptors.…”
Section: Implication Of Atp Hydrolysismentioning
confidence: 87%
“…In respiratory networks, adenosine is clinically significant because it depresses ventilation (Herlenius et al, 1997;Herlenius and Lagercrantz, 1999;Mironov et al, 1999), and is implicated in the hypoxia-induced depression of ventilation (Yan et al, 1995) and apnea in newborns (Runold et al, 1989;Lopes et al, 1994). Our observation that the post-ATP decrease in frequency depends on ATP breakdown suggests that effects of ATP on rhythm will be determined by an interaction between P2 and P1 receptors.…”
Section: Implication Of Atp Hydrolysismentioning
confidence: 87%
“…In studies of anesthetized newborn piglets, it was concluded that adenosine contributes to ventilatory depression caused by hypoxia [175,176]. In another investigation of the role of adenosine in the hypoxic ventilatory response of the newborn piglet, the authors concluded that adenosine plays a central role in modulating ventilation in the newborn piglet and is involved in the biphasic ventilatory responses to hypoxia [177]. It has been claimed that the inspiratory output of XII motor neurons that control the airways in mammals is potentiated by P2Y 1 receptors in neonatal rat in vitro [178].…”
Section: Central Nervous Systemmentioning
confidence: 96%
“…In addition, quantitative real-time polymerase chain reaction was conducted to check whether the functional consequences of diazepam prenatal exposure might reflect changes in the expression of genes encoding for GABA A R. We monitored the transcription levels of its ␣1 and ␣2 subunits because they are constituent of the benzodiazepine binding site, which are the most abundant in the CNS (8) and they exhibit development-dependent expression throughout areas of the brain (9). We also monitored the transcription levels of A 1 and A 2A adenosine receptors (A 1 R and A 2A R) because they are downregulated by chronic administration of diazepam in the adult forebrain (10) and they are crucial for breathing control processes in newborns (11,12), partly via control of endogenous GABA release (13). 1…”
mentioning
confidence: 99%